Preclinical Evaluation of an Imidazole-Linked Heterocycle for Alzheimer's Disease - Andrea Bagán; Sergio Rodriguez-Arévalo; Teresa Taboada-Jara; Christian Griñán-Ferré; Mercè Pallàs; Iria Brocos-Mosquera; Luis F. Callado; José A. Morales-García; Belén Pérez; Caridad Diaz; Rosario Fernández-Godino; Olga Genilloud; et al. (MDPI AG, 2023)
Humanity is facing a vast prevalence of neurodegenerative diseases, with Alzheimer's disease (AD) being the most dominant, without efficacious drugs, and with only a few therapeutic targets identified. In this scenario, we aim to find molecular entities that modulate imidazoline I2 receptors (I2-IRs) that have been pointed out as relevant targets in AD. In this work, we explored structural modifications of well-established I2-IR ligands, giving access to derivatives with an imidazole-linked heterocycle as a common key feature. We report the synthesis, the affinity in human I2-IRs, the brain penetration capabilities, the in silico ADMET studies, and the three-dimensional quantitative structure-activity relationship (3D-QSAR) studies of this new bunch of I2-IR ligands. Selected compounds showed neuroprotective properties and beneficial effects in an in vitro model of Parkinson's disease, rescued the human dopaminergic cell line SH-SY5Y from death after treatment with 6-hydroxydopamine, and showed crucial anti-inflammatory effects in a cellular model of neuroinflammation. After a preliminary pharmacokinetic study, we explored the action of our representative 2-(benzo[b]thiophen-2-yl)-1H-imidazole LSL33 in a mouse model of AD (5xFAD). Oral administration of LSL33 at 2 mg/Kg for 4 weeks ameliorated 5XFAD cognitive impairment and synaptic plasticity, as well as reduced neuroinflammation markers. In summary, this new I2-IR ligand that promoted beneficial effects in a well-established AD mouse model should be considered a promising therapeutic strategy for neurodegeneration.